Building better strategies to develop new medications in Alcohol Use Disorder: Learning from past success and failure to shape a brighter future. (August 2019) - Cannella, Nazzareno; Ubaldi, Massimo; Masi, Alessio; Bramucci, Massimo; Roberto, Marisa; Bifone, Angelo; Ciccocioppo, Roberto
Highlights: The complexity of Alcohol Use Disorder offer the opportunity to explore new targets. The most promising drug targets for alcohol addiction are described. Despite compelling preclinical data many molecules did not show clinical efficacy. Preclinical efficacy of CRF1R antagonists in alcohol abuse did not translate in humans. An integrated approach to translate preclinical to clinical findings is proposed. Abstract: Alcohol Use Disorder (AUD) is a chronic disease that develops over the years. The complexity of the neurobiological processes contributing to the emergence of AUD and the neuroadaptive changes occurring during disease progression make it difficult to improve treatments. On the other hand, this complexity offers researchers the possibility to explore new targets. Over years of intense research several molecules were tested in AUD; in most cases, despite promising preclinical data, the clinical efficacy appeared insufficient to justify futher development. A prototypical example is that of corticotropin releasing factor type 1 receptor (CRF1R) antagonists that showed significant effectiveness in animal models of AUD but were largely ineffective in humans. The present article attempts to analyze the most recent venues in the development of new medications in AUD with a focus on the most promising drug targets under current exploration. Moreover, we delineate the importance of using a more integrated translational framework approach to correlate preclinical findings and early clinical data to enhance the probability to validate biological targets of interest.